Non-Judicial Mechanism for Resolving Past Human Rights Violence in Indonesia; How Does It Redress Women Victims of Sexual Violence? - Eddyono, Sri Wiyanti; Ayuningtyas, Audrey Anggita (The Indonesian Journal of Socio-Legal Studies, 2026)
This paper examines whether the Indonesian government's non-judicial settlement for addressing past gross human rights violations (PGHRV) offers redress for the victims of sexual violence of past human rights violations. Indonesia has grappled to address past human rights violations through formal justice mechanisms. There are about 12 unresolved cases, more than half of which concerning sexual violence during conflict. This paper combined a socio-legal approach with mixed methods to gather data on the issue PGHRV: desk research and interviews with key persons involved in the non-judicial mechanism. Due to the heavy political pressure, the formal judicial mechanism reached a dead end. As alternatives the Indonesian government in 2022 established a team for the non-judicial resolution of past gross human rights violations (Tim PPHAM) and in 2023 the monitoring team for the implementation of the recommendation to resolve past gross human rights violations. However, the outcomes of the non-judicial settlement for victims of sexual violence are questionable. We conclude that the mechanism was not properly designed to offer redress for victims but was heavily influenced by political interests, causing distrust among the victims participating in it.  It was the victims who decided to remain silent, yet it was the structure of the non-judicial mechanism that silenced them. The space victims most trust is the National Commission on Violence Against Women, but unfortunately the Commission does not have the authority and capacity to document gross human rights violations, nor to redress the victims of sexual violence.